Recommender systems using temporal restricted sequential patterns - Samamé Jimenez, Hilda Ana (Pontificia Universidad Católica del Perú, 2021)
Recommendation systems are algorithms for suggesting relevant items to users. Generally, the recommendations are expressed in what will be recommended and a value representing the recommendation's relevance. However, forecasting if the user will buy the recommended item in the next day, week, or month is crucial for companies. The present study describes a process to suggest items from sequential patterns under temporal restrictions.
Keywords: Minería de datos; Procesamiento secuencial (Computación); http://purl.org/pe-repo/ocde/ford#1.02.01